Improving safety in paediatric thyroidectomy by PTH measurements. (16th July 2021) - Freire, Analía V.; Ropelato, María G.; Papendieck, Patricia; Vieites, Ana; Elías, Eugenia; Ballerini, Maria G.; Rodriguez, María E.; Bergadá, Ignacio; Chiesa, Ana
Abstract: Objetive: We followed our previously reported algorithm based on intra and postoperative parathyroid hormone (PTH) levels to predict postthyroidectomy hypoparathyroid hypocalcemia. The objective of the study was to assess if this strategy is useful and safe to reduce hypocalcemia, hospitalisation length and postsurgery calcium sampling. Design, Patients, Meassurements: We classified our series of 66 patients according to their risk of hypoparathyroidism based on PTH determinations. We treated high‐risk patients with calcium and vitamin D1–25 supplementation and obtained routine daily calcium samples to control low‐risk patients until 48 h postsurgery. We compared the outcomes and overall results of this new approach with those of a historical control group of patients with equivalent PTH measurements who were treated only if they presented hypocalcemia. Results: In the high‐risk subgroup ( n  = 30), five patients had hypocalcemia within the first 24 h. Compared with the high‐risk control subgroup, the incidence of hypocalcemia fell from 100% to 17% ( p  < .001), and the median hospitalisation length from 6 to 3 days ( p  < .001). In the low‐risk subgroup ( n  = 36), 28 patients remained normocalcemic with significantly less calcium sampling ( p  < .001). Eight patients had hypocalcemia; seven of them required neck dissection, which was the only risk factor related to postsurgical hypoparathyroidism (RR: 2.1 [confidence interval 95%: 1.4–3.1]; p  < .001). The overall incidence of hypocalcemia decreased by 58% in our patients compared to the control group. Conclusions: Assessing PTH levels to classify the risk of hypoparathyroidism and to initiate preventive therapy was an effective approach that improved the safety of our paediatric patients by reducing the incidence of hypocalcemia and the length of hospitalisation after thyroidectomy in paediatric patients.